Beyond the Deepwoods [compact disc, unabridged] - Stewart, Paul, 1955- (Stewart, Paul, 1955- Edge chronicles (Listening Library), 2005)
Thirteen-year-old Twig, having always looked and felt different from his woodtroll family, learns that he is adopted and travels out of his Deepwoods home to find the place where he belongs.